Consumer Education Through Green marketing - Rasyid, Hanindito; Hudrasyah, Herry (Journal of Business and Management, 2012)
Global warming is currently an issue that is often heard. The greenhouse effect that takes place when solar radiation is trapped within the earth’s atmosphere creates a rise of temperature at a global scale. The effects of global warming itself comes from none other than human consumerism. The amount of waste that people dispose are so much that the earth could not handle it anymore. Marketers should also take responsibility for preventing this from getting worse, because the consumerist lifestyle itself comes from increasing demands influenced by marketers. Therefore, marketers are responsible to shift the consumers lifestyle to become more environmental friendly.This research will focus on college students as the main research subject because they will be the next generation that will make the decisions which will affect the environment for the future.There are two main goals of the research which are to find out the consumers current level of knowledge regarding green products and what are able to motivate them in purchasing a product.The research shows that most consumers already know that products, specifically shampoo, that come in a reusable form of packaging and are made from organic materials are environmental friendly, but do not perceive the same with products that use less water. As for their purchasing motive, it turns out that the environmental friendliness of a product and brand ambassador are the two main factors that separate people with lower level of knowledge regarding green products to those who are more aware itKeywords – Green Marketing; Consumer EducationCategory: Marketing; Business Strategy